PENGARUH KOMITMEN ORGANISASI, KUALITAS PELAYANAN DAN KINERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT PADA LEMBAGA PEMASYARAKATAN KELAS IIA PADANG - Yozi Rahmat Denus; Yulihasri Yulihasri (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine the effect of organizational commitment, service quality, and employee performance on community satisfaction on employees of the Class IIA Padang Penitentiary. The method used in this research is quantitative research with a descriptive approach. The population in this study were employees of the Class IIA Penitentiary in Padang. The sample used was 144 people using a saturated sampling technique (census). The data analysis technique is multiple linear regression. The results showed that: (1) Organizational commitment has a positive and significant effect on community satisfaction. (2) Service quality has a positive and significant effect on community satisfaction. (3) Employee performance has a positive and significant effect on community satisfaction. (4) Organizational commitment, service quality, employee performance together have a positive and significant effect on community satisfaction in the Class IIA Padang Penitentiary.